Implementasi Program Kesehatan Reproduksi Remaja melalui Posyandu Remaja: Studi Kualitatif - Pandawa, Rugaya; Djama, Nuzliati T (Poltekkes Kemenkes Padang, 2023)
Utilization of youth information services is still low in several areas, including North Maluku. The low level of utilization of reproductive health services among adolescents is influenced by many factors. This research aims to analyze the implementation of adolescent reproductive health programs. Through the youth Posyandu in Juanga Village, the working area of the Daruba Community Health Center, South Morotai District. This research used qualitative methods, selecting subjects using purposive sampling and data collection techniques through observing the implementation of youth Posyandu, interviews, and focus group discussions on cadres. The research subjects were 14 informants, consisting of five cadres, five teenagers, two families, one health center officer, and one community figure. The findings show that there is no special training for adolescent Posyandu cadres, there is no incentive funding for cadres, the infrastructure and guidelines are incomplete, and there is still a lack of knowledge among adolescents regarding adolescent reproduction. It can be concluded that the current implementation of youth Posyandu has obstacles and problems which have an impact on implementation limitations, including the implementation process which still experiences obstacles in attracting youth participation and communication with related parties, as well as obstacles to funding incentives for youth cadres. It is recommended that there be a model of community empowerment, especially teenagers, in utilizing youth Posyandu, in an effort to reduce the high rate of premarital teenage pregnancies.